A Cross-Sectional Online Survey of Knowledge, Attitudes and Practices about Tuberculosis among Homoeopathy Practitioners and Students in India - Mittal, Renu; Taneja, Divya; Khurana, Anil (Homœopathic Links, 2022)
Background Homoeopathy is the second most popular healthcare system in our country with 0.3 million practitioners. Among healthcare providers, homeopathic practitioners (HPs) are also the first contact care providers and often see tuberculosis (TB) patients. To align these practitioners with the National Strategic Plan 2017 to 2025, it is essential that their knowledge and skills about TB is assessed.Objectives The aim of this study was to assess the knowledge, attitude and practice (KAP) of HPs and students in India about TB.Methods An online cross-sectional survey conducted from 3rd to 17th May 2020 identified socio-demographic data, KAP. Descriptive and inferential statistics was performed to analyse differences based on socio-demographic variables.Results Out of 1,784 responses received, 72% were practitioners and 28% were students pursuing homoeopathy course. Eighty per cent respondents were aware of suspected case of TB, miliary, extensive drug-resistant TB and Directly Observed Treatment Short plus regimen for multidrug resistance TB. Knowledge scores significantly differed with qualification, type and years of practice (p = 0.001). Significant differences in attitude of government and private practitioners were noted on issues related to diagnosis and treatment management of TB patients (78.9 vs. 69.3%; p = 0.02).Conclusion The findings could be considered as baseline indicators in relation to the current KAP on TB among HPs. Specific training programmes can be developed for their active involvement in TB diagnosis and management so that TB prevention and care can be improved.
Keywords: tuberculosis; KAP; homoeopathy